2022
DOI: 10.1007/s11912-022-01333-w
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dynamin-Related Protein Drp1: a New Player in Cardio-oncology

Abstract: Purpose of Review This study is aimed at reviewing the recent progress in Drp1 inhibition as a novel approach for reducing doxorubicin-induced cardiotoxicity and for improving cancer treatment. Recent Findings Anthracyclines (e.g. doxorubicin) are one of the most common and effective chemotherapeutic agents to treat a variety of cancers. However, the clinical usage of doxorubicin has been hampered by its severe cardiotoxic side effects leading to heart fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 136 publications
0
3
0
Order By: Relevance
“…Mitochondria are abundant in hepatocytes . Drugs can directly or indirectly destroy the structure or function of mitochondria, resulting in accumulation of ROS, imbalance of Ca 2+ homeostasis, disappearance of MMP, and changes in mitochondrial membrane permeability, which ultimately leads to severe hepatotoxic effects .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondria are abundant in hepatocytes . Drugs can directly or indirectly destroy the structure or function of mitochondria, resulting in accumulation of ROS, imbalance of Ca 2+ homeostasis, disappearance of MMP, and changes in mitochondrial membrane permeability, which ultimately leads to severe hepatotoxic effects .…”
Section: Resultsmentioning
confidence: 99%
“…41 It has been reported that the Ca 2+ levels are closely related to the ROS concentration, as ROS can regulate intracellular Ca 2+ signaling via multiple channels. 42 ATP plays an important role as an essential source of energy in various biological processes within 44 Drugs can directly or indirectly destroy the structure or function of mitochondria, resulting in accumulation of ROS, imbalance of Ca 2+ homeostasis, disappearance of MMP, and changes in mitochondrial membrane permeability, which ultimately leads to severe hepatotoxic effects. 45 The decline in the MMP is a hallmark event in the early stages of apoptosis.…”
Section: Combined Cytotoxicity Of Enns and Donmentioning
confidence: 99%
“…Drp1, mitochondrial fission regulator, is upregulated in damaged cardiac tissues induced by doxorubicin. A study showed that Drp1 inhibitor will be a promising pharmacological agent, which inhibits the excessive mitochondrial fission mediated by doxorubicin and ameliorates its cardiotoxicity ( 79 ). Drp1 deficiency in adult mouse hearts showed the pathophysiological consequences of progressive ventricular enlargement and functional decompensation, resulting in heart failure ( 80 ).…”
Section: Introductionmentioning
confidence: 99%